Respon Mahasiswa Terhadap Penyelesaian Soal Koneksi Matematis Melalui Taksonomi Fink - Kanisius Mandur; Fransiskus Nendi; Fulgensius Efrem Men; Silfanus Jelatu (Jurnal Pendidikan Matematika (JPM), 2021)
Student response is an important aspect of learning because it helps educators understand student development. One of the frameworks used to analyze student responses to cognitive, affective, and metacognitive aspects is the Fink taxonomy. This study aims to find patterns of student response rates in solving mathematical connection through Fink's taxonomy. This research method is qualitative. The data collected were data on the ability of mathematical connections to measure student responses to cognitive and metacognitive aspects taken using test instruments as well as data on social and caring dimensions to measure student responses to affective aspects that were taken using questionnaires. The results of this study are student responses at the basic knowledge level of 18.42%, application of 12.79%, integration of 12.22%, social dimensions 23.28%, caring aspects of 22.34%, and metacognitive 10.95. % and student response results at the level of basic knowledge of 18.94%, application of 13.16%, integration of 11.23%, social dimensions 23.87%, caring aspects of 22.78%, and metacognitive of 10.02%. Student responses to cognitive, affective, and metacognitive aspects provide an overview for educators to pay attention to students' abilities and attitudes in building knowledge independently on a subject matter.